Cosmic rays escape from their sources - Marcowith, A. (Frontiers in Astronomy and Space Sciences, 2025)
Cosmic rays (CRs) are accelerated in diverse astrophysical objects like supernova remnants, massive star clusters, or pulsars. Fermi acceleration mechanisms built a power-law distribution controlled by the ratio of the acceleration to escape timescales in the acceleration site. Hence, escape is an essential mechanism to establish the particle distribution at cosmic-ray sources and to control the flux of cosmic rays injected into the galaxy. Different models have tried to account for the escape process. However, all show some limitations due to the complexity of the particle release mechanism, usually involving 3D geometry, with specific magnetic turbulence properties linked to the process itself. The escape process is also time dependent and results from the interplay of particle acceleration and injection efficiency in the astrophysical source. Once injected into the interstellar medium, freshly released particles are channelled by the ambient magnetic field, which is itself turbulent. In a simplified view, we mainly focus on the propagation of CRs along 1D magnetic flux tubes before turbulent motions start to mix them over a turbulent coherence length, and then we further question this assumption. Close to their sources, one can also expect cosmic rays to harbour higher pressure with respect to their mean value in the interstellar medium. This intermittency in the CR distribution is prone to trigger several types of kinetic and macro instabilities, among which the resonant streaming instability has been the most investigated. In this article, we review recent observational and theoretical studies treating cosmic-ray escape and propagation in the vicinity of their source. We will consider three main astrophysical contexts: association with massive star clusters, gamma-ray halos around pulsars, and, more specifically, supernova remnants. In particular, we discuss in some detail the cosmic-ray cloud (CRC) model, which has been widely used to investigate CR propagation in the environment of supernova remnants. The review also discusses recent studies on CR-induced feedback over the interstellar medium surrounding the sources associated with the release process, as well as alternative types of driven instabilities.